2020
DOI: 10.1186/s12985-020-01423-w
|View full text |Cite
|
Sign up to set email alerts
|

Male papillomavirus infection and genotyping in the Qingyuan area

Abstract: Background This study aims to screen the male human papillomavirus (HPV) infection status and genotyping in Qingcheng District, Qingyuan City, Guangdong Province, China to provide a reference basis for formulating prevention strategies for HPV infection. Methods The present study collected urethral epithelium or scraped penile epidermis from high-risk male patients in Qingyuan People's Hospital during the last five years, extracted DNA fragments using the boiling method, and detected 23 types of HPV genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(27 reference statements)
2
3
1
Order By: Relevance
“…Our study found that 82.22% (1,336/1,625) of the cases had an age distribution of ≤ 24, 25–34, and 35–44, which may be related to the level of sexual activity. This study found no significant difference in HPV detection rates among different age groups, which is different from a previous study of high-risk male HPV infected individuals ( Yin et al, 2020 ), This may be related to the fact that the research subjects of this study are male and female patients with genital warts. In addition, long-term and persistent HPV infection may pose a risk of cancer transformation, so it is necessary to conduct comprehensive and regular screening for elderly people infected with HPV ( Sudenga et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our study found that 82.22% (1,336/1,625) of the cases had an age distribution of ≤ 24, 25–34, and 35–44, which may be related to the level of sexual activity. This study found no significant difference in HPV detection rates among different age groups, which is different from a previous study of high-risk male HPV infected individuals ( Yin et al, 2020 ), This may be related to the fact that the research subjects of this study are male and female patients with genital warts. In addition, long-term and persistent HPV infection may pose a risk of cancer transformation, so it is necessary to conduct comprehensive and regular screening for elderly people infected with HPV ( Sudenga et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The top five HPV genotypes were HPV-52, HPV-58, HPV-16, HPV-51, and HPV-66, which was consistent with the data generated by some Chinese population-specific investigations [ 4 , 10 , 11 ]. A study conducted in Guangdong Province, China showed that the top five prevalence of high-risk HPV genotypes among males were HPV-16, HPV-18, HPV-31, HPV-33, and HPV-35 [ 10 ]. Another study conducted in southern China showed that the most common HPV genotypes among males were HPV-58, HPV-52, and HPV-16 [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…HPV infection among male has significantly increased the risk of cervical cancer in their sexual partners [ 4 , 10 , 11 ]. Although the majority of men with HPV infection were asymptomatic or subclinical cases, HPV still caused malignant diseases such as anal or penile cancer in men [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This retrospective study presents the inaugural estimate of genital HPV infection prevalence among outpatient men in Guangzhou, China, revealing an overall prevalence of 42.15% with variations ranging from 29.55% to 81.31% across distinct diagnostic populations. Comparisons with other regions in China indicate similarities with the 42.0% prevalence reported among men in Shandong, 18 but lower rates compared to Qingyuan (54.3%) 19 and Shanghai (58.4%), 20 and higher rates compared to Anyang (17.5%) 21 and Liuzhou (9.4%). 22 Additionally, a previous systematic review encompassing 65 HPV prevalence studies from 35 countries estimated the global overall HPV prevalence among men to be 31%, with study-specific prevalence varying widely from 1% to 84% among low-risk men and from 2% to 93% among high-risk men.…”
Section: Discussionsupporting
confidence: 55%